The Impact of Linguistic Diversity on the Social Justice and Equity Pedagogy to Knowledge Construction - Heyder Sabir Hasan; Ali Mahmood Jukil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Linguistic Diversity (LD) refers to linguistic variety. Here, it refers to the students’ functional linguistic or sociolinguistic academic and non-academic linguistic variation. Also, social justice and equity pedagogy are the representations of equal opportunities that ensure equal and constant development which leads to knowledge re/constructions. Ecologically in and out of the institutional settings of Humanity Sciences studies (HSs) the situation is diverse linguistically and sub/culturally. The problem is that the humanity sciences students are supposed to be linguistically and professionally proficient and knowledgeable but the language policy, plan and practice do not assist them to reach their higher education standards. So the questions are: Is LD implemented properly? Does the LD lead to knowledge re/construction and development? How is the social justice and equity pedagogy in the processes of teaching, leaning and classroom management? The hypothesis is that the LD is not implemented as it is and as the requirements and needs of students. So the graduates might not be skillfully and academically prepared locally, nationally and internationally. The study aims at finding the sociolinguistic diversity obstacles that affect teaching, learning and developmental knowledge construction via the investigation of the degree of social justice, equity pedagogy and distinctive individuals’ identity. A questionnaire was constructed on the basis of the correlated contents of the study and some absolutely related resources. The items ask the quantitative and qualitative attitudes and perspectives of the senior students who are towards the topic. The participants are the seniors at the HSs at Salahaddin University- Erbil (SU-E) who are diverse linguistically and culturally. Their attitudes can be reliable and valid because they had had experiences the university learning process strengths and weaknesses. It has been confirmed and concluded that the de facto or LD praxis of implementation requires more accurate related techniques of teaching, learning and socialization processes. Because the students approve that they are not actively and skillfully learnt the academic languages, also, problems of social justice and equity pedagogy so that it does not help the students to have the ability to comprehend the contents of the curricula and have the ability to enroll in the lifelong national and international developmental knowledge reconstruction and creative constructions, careers of marketing and academic professional proficiencies